Ag and Al2O3/water two-phase transient flow analysis in a double-pipe heat exchanger equipped with baffles and rotating inner tube - Mohammed Al-Saad; Ali B.M. Ali; Mohammed Al-Mosallam; Mohammad N. Fares; Mohammad Ali Fazilati; Soheil Salahshour; Rozbeh Sabetvand (Case Studies in Chemical and Environmental Engineering)
Considering the wide application of double-pipe heat exchanger made their performance improvement very important. Employing aqueous nanofluid (NF) of Ag and Al2O3 as the working fluid inside the inner tube of the heat exchanger and its rotation as the respective passive and active enhancing methods are investigated numerically using the two-phase mixture method. The sensitivity analysis was performed to reveal the effect of Reynolds (Re) number, NF concentration and tube rotational speeds on heat transfer coefficient, heat transfer effectiveness, and efficiency ratio. The Re number, NF concentration, and rotation speed lie in 1000-3000, 0–4 %, and 300–500 rpm, respectively. The results show the higher improving effect of Ag rather than Al2O3 nanoparticle; for Re = 1000, 1500 and 2000 the efficiency ratio averaged between different concentrations are 39 %, 30 %, 20 % for Al2O3/water and 62 %, 65 % and 26 % for Ag/water NFs, respectively. By increasing the Re number, the enhancing effect of velocity increment on heat transfer rate prevails and hinders that of employing NF. Also, in rotating mode, the enhancement made by increasing the Re number is higher in the rotation speed of 500 rather than 300 rpm. The overall change of efficiency ratio versus the Re number increment is decreasing and the greatest improving effect of using NF is for the lowest Re numbers. Also, the enhancement due to increasing the Re number increment is higher at a rotational speed of 500 rather than 300 rpm.